NEW APPROACHES TO THE PATRIOTISM EDUCATION AND UPBRINGING OF YOUTH BASED ON KARAKALPAK FOLK PEDAGOGY - Orazımbetov, E.K. (SCIENCE and SOCIETY, 2026)
This article presents a pedagogical analysis of the exceptional significance of Karakalpak folk pedagogy in preparing youth for future life. It highlights how the concepts of modesty and virtue embodied by girls, as well as the courage and determination demonstrated by boys, are reflected in traditional educational practices. The study also validates the pedagogical potential of Karakalpak folk pedagogy in fostering patriotic consciousness among young people within the context of contemporary globalization..